THE EFFECT OF N, P, K ON SOIL CHEMICAL COMPOSITION AND YIELD OF ROBUSTA COFFEE (COFFEA CANEPHORA PIERRE) - OJENIYI, S. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
One hundred and twenty-eight soil were in 1978 from within 30cm depth of 64 NPK treated plots. A 4 x 4 x 2 NPK trial replicated 2 times commenced in 1972. Three harvests of coffee berry were collected from the treated plots in 1978. Values of coffee yield were correlated with resultant of soil N, P, K, (K + Ca + Mg) concentration, pH and organic matter. positive correlations between coffee yield and. soil N and P were observed. Positive correlations were observed between yield and soil organic matter, though the correlations were not significant. In most cases negative correlations were observed between yield and base elements. Negative correlations between yield and base elements are discussed in relation to observed low Mg/K ratio and the non-u% of fertilizers containing Mg and Ca. It appeared that soil analysis result indicate the potential of soil to furnish the. crop with nutrients in the near future rather than immediately.